SARS-CoV-2 booster vaccination rescues attenuated IgG1 memory B cell response in primary antibody deficiency patients - Lin, Frank J.; Doss, Alexa Michelle Altman; Davis-Adams, Hannah G.; Adams, Lucas J.; Hanson, Christopher H.; VanBlargan, Laura A.; Liang, Chieh-Yu; Chen, Rita E.; Monroy, Jennifer Marie; Wedner, H. James; Kulczycki, Anthony; Mantia, Tarisa L.; et al. (Frontiers in Immunology, 2022)
Although SARS-CoV-2 vaccines have proven effective in eliciting a protective immune response in healthy individuals, their ability to induce durable immune response in immunocompromised individuals remains poorly understood. Primary antibody deficiency (PAD) syndromes are among the most common primary immunodeficiency disorders in adults and are characterized by hypogammaglobulinemia and impaired ability to mount robust antibody responses following infection or vaccination. Here, we present analysis of both the B and T cell response in a prospective cohort of 30 individuals with PAD up to 150 days following initial COVID-19 vaccination and 150 days post mRNA booster vaccination. After primary vaccination series, many of the individuals with PAD syndromes mounted SARS-CoV-2 specific memory B and CD4+ T cell responses that overall were comparable to healthy individuals. Nonetheless, individuals with PAD syndromes had reduced IgG1+ and CD11c+ memory B cell responses following the primary vaccination series, with the defect in IgG1 class-switching rescued following mRNA booster doses. Boosting also elicited an increase in the SARS-CoV-2-specific B and T cell response and the development of Omicron-specific memory B cells in COVID-19-naïve PAD patients. Individuals that lacked detectable B cell responses following primary vaccination did not benefit from booster vaccination. Together, these data indicate that SARS-CoV-2 vaccines elicit memory B and T cells in most PAD patients and highlights the importance of booster vaccination in immunodeficient individuals.